Carbon Dioxide Removal Policy in the Making: Assessing Developments in 9 OECD Cases - Schenuit, Felix; Colvin, Rebecca; Fridahl, Mathias; McMullin, Barry; Reisinger, Andy; Sanchez, Daniel L.; Smith, Stephen M.; Torvanger, Asbjørn; Wreford, Anita; Geden, Oliver (Frontiers in Climate, 2021)
Since the adoption of the Paris Agreement in 2015, spurred by the 2018 IPCC Special Report on Global Warming of 1.5°C, net zero emission targets have emerged as a new organizing principle of climate policy. In this context, climate policymakers and stakeholders have been shifting their attention to carbon dioxide removal (CDR) as an inevitable component of net zero targets. The importance of CDR would increase further if countries and other entities set net-negative emissions targets. The scientific literature on CDR governance and policy is still rather scarce, with empirical case studies and comparisons largely missing. Based on an analytical framework that draws on the multi-level perspective of sociotechnical transitions as well as existing work on CDR governance, we gathered and assessed empirical material until early 2021 from 9 Organisation for Economic Cooperation and Development (OECD) cases: the European Union and three of its Member States (Ireland, Germany, and Sweden), Norway, the United Kingdom, Australia, New Zealand, and the United States. Based on a synthesis of differences and commonalities, we propose a tripartite conceptual typology of the varieties of CDR policymaking: 1) incremental modification of existing national policy mixes, 2) early integration of CDR policy that treats emission reductions and removals as fungible, and 3) proactive CDR policy entrepreneurship with support for niche development. Although these types do not necessarily cover all dimensions relevant for CDR policy and are based on a limited set of cases, the conceptual typology might spur future comparative work as well as more fine-grained case-studies on established and emerging CDR policies.